2011
DOI: 10.1007/s10528-011-9454-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of B3GNT5 Polymorphisms with Susceptibility to ETEC F4ab/ac in the White Duroc × Erhualian Intercross and 15 Outbred Pig Breeds

Abstract: The B3GNT5 gene is a candidate for the F4ab/ac receptor conferring susceptibility to enterotoxigenic Escherichia coli (ETEC) F4ab/ac in pigs. In this study, we screened mutations in the complete coding region of the porcine B3GNT5 gene and identified four SNPs in the 3' untranslated regions. We genotyped the four SNPs across a large-scale White Duroc × Chinese Erhualian F2 resource population (total F2 = 755) and 292 purebred piglets representing 15 Chinese and Western breeds. We found that the g.1476G→A locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…For ETEC F4, single nucleotide polymorphisms (SNPs) located on Mucin4 ( MUC4 ) [48], on Mucin 13 ( MUC13 ) [49, 50], Mucin 20 ( MUC20 ) [51], the transferrin receptor ( TFRC ) [52], tyrosine kinase non-receptor 2 ( ACK1 ) [53], UDP-GlcNAc:betaGal beta-1,3-N-acetylglucosaminyltransferase 5 ( B3GNT5 ) [52] genes have been proposed as genetic markers for pig ETEC resistance/susceptibility. Goetstouwer et al [54] have recently proposed new SNPs located on the candidate region (chr13: 144810100-144993222) as new determinates for ETEC F4 susceptibility.…”
Section: Setting Of the Challenge Modelmentioning
confidence: 99%
“…For ETEC F4, single nucleotide polymorphisms (SNPs) located on Mucin4 ( MUC4 ) [48], on Mucin 13 ( MUC13 ) [49, 50], Mucin 20 ( MUC20 ) [51], the transferrin receptor ( TFRC ) [52], tyrosine kinase non-receptor 2 ( ACK1 ) [53], UDP-GlcNAc:betaGal beta-1,3-N-acetylglucosaminyltransferase 5 ( B3GNT5 ) [52] genes have been proposed as genetic markers for pig ETEC resistance/susceptibility. Goetstouwer et al [54] have recently proposed new SNPs located on the candidate region (chr13: 144810100-144993222) as new determinates for ETEC F4 susceptibility.…”
Section: Setting Of the Challenge Modelmentioning
confidence: 99%
“…Previous studies revealed that the loci controlling F4ab/F4ac receptor is located on SSC13q41 (reviewed in [70]). Mutations in functional genes including HEG1 , ITGB5 [65], MUC4 [71,72], FUT1 [73,74], B3GNT5 [75,76], MUC20 [77], and MUC13 [18] were found to be associated with porcine susceptibility. Jacobsen et al [91] characterized 34 SNPs in five candidate genes within the ETEC F4ab/ac candidate region, but no obvious causative mutations were identified for E. coli F4ab/F4ac susceptibility.…”
Section: Genetic Control Of Porcine Resistance To Gram-negative Bacilmentioning
confidence: 99%